Presumed tuberculous keratopathy: a rare presentation of “serpiginious-like” keratic precipitates in a unilateral anterior uveitis case - Gaayathri N,; Wong, HS; Che Muhaya Muhamad,; Hazlita Mohd Isa, (Faculty of Medicine, Universiti Kebangsaan Malaysia Medical Centre, 2016)
A 43-year-old lady with no underlying medical illness was referred for chronic recurrent unilateral anterior uveitis. She had no previous ocular trauma or surgical intervention to the eye. Upon presentation, she was found to have unilateral anterior uveitis with a very unusual “serpiginious-like” pattern of keratic precipitate. Initial investigations revealed no infective cause and patient was commenced on topical and oral steroids. Unfortunately, her ocular symptoms worsened and developed steroid induced glaucoma. A repeat infective screening revealed positive results for tuberculosis. Patient has since responded very well to treatment with antitubercular agents with complete resolution of the inflammation and good visual recovery. In this case report, we wish to emphasize that ocular tuberculosis presentation is highly variable and in such cases its best to employ a high index of suspicion to initiate the right treatment timely. An infective etiology should promptly be suspected in patients who are not showing response to topical or systemic steroids. Even in an immunosuppressed state, ocular tuberculosis may remain unilateral throughout the course of the disease, as seen in the patient. Injudicious use of steroid can make a simple anterior granulomatous uveitis progress to florid granulomatous uveitis with confluent keratic precipitates.